Validação de jogo educativo para construção do conhecimento de adolescentes acerca da prevenção de DST/AIDS - Scopacasa, Ligia Fernandes (2013)
Adolescence is a stage of life characterized by several events. One of the most important is the sexual activity. But due to the resulting changes at the adolescent process, sexual practices, in many cases, are made of unprotected form, as a result of it, teenagers are becoming more vulnerable to sexual diseases like STD / AIDS. In order to prevent this, the nurse comes up to try to intervene with this group in order to prevent and inform them about STD / AIDS. One way to achieve this is through health education that can make use of educational technologies in their practice. Among the various types of educational technologies highlighted, the educational game, due to its dynamic and entertaining features, favors the teaching-learning process of adolescents, being an important tool in the prevention of STD / AIDS in adolescence. This study aimed to validate an educational game built to help with the prevention of adolescent STD / AIDS in public schools of Fortaleza city, and also to compare the acquisition of knowledge of adolescents regarding STD / AIDS educational game using the expository lecture and regular class. It was a quasi-experimental study with a quantitative approach that was divided into two phases, the first of which was composed of 120 adolescents and the second of, initially, 198 adolescents. The first phase included the construction of a pre- and a post-test that were used in the next step. However, the second step was the application of the intervention itself, and one group received the educational game that addressed to the prevention of STD / AIDS, the second group also attended an illustrated lecture on the same topic and the third group class taught in the classroom by the teacher responsible for the group . The three groups responded to the pretest before the educational intervention and the posttest twentieth day following the intervention performed. Data analysis was based on statistical tests of the Software Statistical Package for Social Sciences (SPSS) version 17.0 for Windows. Considered significant inferential statistical analysis at p < 0.05 . It is noted that the analysis was also based on the literature on the topic. This research meets the ethical aspects, being approved with the number 229 369 protocol. The first stage of this research contained the pre- and post-tests, each one composed by ten multiple-choice questions, which were derived from a previous thirty question questionnaire. Regarding the second step, no statistically significant differences in the results were found among the variables ‘gender’ (p value 0.168), ‘grade’ (p value 0.509), ‘dwelling’ (p value 0.905) and ‘early sexual activity’ (p value 0.695). In regard to statistically significant differences between the application of the educational game, the expository lecture and the regular class, no relevant distinction was noticed through the results of the educational game and the expository lecture, for their average score were 2.1 and 2.45 respectively. However, when compared the results of the game to those of the group that did not receive a specific intervention, a difference was noticed in the outcome (p value <0.001). Through this study it was concluded that the educational game assists in the educational process of the adolescent as well as the illustrated lecture, however rather than any specific activity in the prevention of STD / AIDS.